Impact of Kangaroo Mother Care on Outcome of Very Low Birthweight Preterm Newborns in a Tertiary Hospital in Abakaliki, Nigeria - Ezeanosike, Obumneme; Daniyan, Olapeju; Anyanwu, Onyinyechukwu; Asiegbu, Uzoma; Ezeonu, Chinonyelum; Onwe-Ogah, Emeka; Onyire, Onyire (Journal of Nepal Paediatric Society, 2019)
Introduction: KMC was developed for care of preterm and low birth weight babies due to shortage of staff and inadequate incubator care enabling early discharge from the hospital for close follow-up at home. It is essential in resource-limited countries where there is epileptic power supply. Therefore, strengthening the evidence for KMC becomes imperative in these resource-limited and adverse cultural regions. Methods: The KMC register of the Newborn Special Care Baby Unit of a tertiary hospital was used to analyse records from January 2016 to February 2018. A total of 55 preterm babies enrolled into KMC were studied. The age and parity of the mother, sex, birth weight, admission and discharge temperatures and weights, duration of KMC per day was retrieved from the KMC register. Results: The mothers’ ages ranged from 18 to 40 years (mean 28.6 ± 6.2 years) with 34% being inexperienced first-time mothers and 10% grand multipara. The birth weights of the babies ranged from 0.9 kg to 2.5 kg. Primiparous women were more likely to do KMC for longer durations. A linear regression model showed that the duration of KMC was related to parity. (R2 = 0.12, p = 0.02). On average there was significant weight gain on discharge with a paired t-test (t = 5.881, df = 44) comparing the discharge and commencement weights showing a mean difference of 0.123 kg (CI 0.081 kg, 0.165 kg, p < 0.001). Conclusions: KMC impacts positively on all parameters of the extremely LBW and premature babies and the duration of KMC is positively associated with better outcome.